MANFAAT BAHAN ORGANIK DAN PERAN CACING TANAH DALAM MENJAGA KESUBURAN TANAH - Sari, Rika; Meiravy Herista Cantika; Muhammad Yusuf Budi Prakoso; Dwi Wahyu Putri; Agil Nurul Hidayah; Muhammad Tsalsa Afriansyah; Nazwa Azizah Zahra; Danny Dwi Saputra (Abdi Techno, 2025)
Soil fertility decline has become a major challenge in the agricultural sector in East Java, particularly in sugarcane monoculture land of Tiru Kidul Village, Kediri. The low organic matter content, resulting from unsustainable land management, has led to decreased crop productivity, as indicated by hardened and barren soils. A team of faculty members and students from the Faculty of Agriculture at Brawijaya University conducted a Community Service Program to disseminate the importance of utilizing organic matter/crop residues to maintain soil fertility to farmers. Through a participatory and innovative approach using a planarcage demonstration tool, farmers were encouraged to observe directly the role of litter (plant residues) and earthworms in preserving soil fertility. Farmers observed that earthworm activity in planarcage with added organic matter (OM) was more active than without OM inputs. They also directly witnessed how earthworms increase soil porosity. Based on evaluation results, farmers' understanding of the role of litter and the positive benefits of earthworms improved. Negative perceptions of earthworms, which were thought to harm crops by consuming roots and soil, were clarified. With the increased awareness among farmers regarding the importance of returning organic matter (crop residues) to agricultural land, this initiative can promote more sustainable, environmentally friendly farming practices while maintaining long-term soil productivity.